Impact of systemic sclerosis oral manifestations on patients' health‐related quality of life: A systematic review. (5th July 2018) - Smirani, Rawen; Truchetet, Marie‐Elise; Poursac, Nicolas; Naveau, Adrien; Schaeverbeke, Thierry; Devillard, Raphaël
Abstract : Background: Oropharyngeal features are frequent and often understated in the treatment clinical guidelines of systemic sclerosis in spite of important consequences on comfort, aesthetics, nutrition and daily life. The aim of this systematic review was to assess a correlation between the oropharyngeal manifestations of systemic sclerosis and patients' health‐related quality of life. Methods: A systematic search was conducted using four databases [PubMed ®, Cochrane Database ®, Dentistry & Oral Sciences Source ® and SCOPUS ® ] up to January 2018, according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses. Grey literature and hand search were also included. Study selection, risk bias assessment (Newcastle‐Ottawa scale) and data extraction were performed by two independent reviewers. The review protocol was registered on PROSPERO database with the code CRD42018085994. Results: From 375 screened studies, 6 cross‐sectional studies were included in the systematic review. The total number of patients included per study ranged from 84 to 178. These studies reported a statistically significant association between oropharyngeal manifestations of systemic sclerosis (mainly assessed by maximal mouth opening and the Mouth Handicap in Systemic Sclerosis Scale) and an impaired quality of life (measured by different scales). Studies were unequal concerning risk of bias mostly because of low level of evidence, different recruiting sources of samples and different scales to assess the quality of life. Conclusion: This systematic review demonstrates a correlation between oropharyngeal manifestations of systemic sclerosis and impaired quality of life, despite the low level of evidence of included studies. Large‐scaled studies are needed to provide stronger evidence of this association.